OPTIMIZATION OF LEADING PROGRAMS OF BALI PROVINCIAL GOVERNMENT TO BALI MANDARA - Desti Nur Amalia; Panji Kusuma Prasetyanto (Jurnal Paradigma Multidisipliner (JPM), 2020)
This study aims to inspect about “Optimalisasi Program Unggulan Pemerintah Provinsi Bali Menuju Bali MANDARA”, In Bali. The research utilises direct methode or KLKI with qualitative data, acquired by Badan Pusat Statistik. This case appropriate with conceptual system excellent program concern to Bali Mandara. Datas from the research explain that Bali Province publish an excellent program concern to Bali MANDARA which has intention to actualize Bali which are Maju, Aman, Damai, Sejahtera. This study used the superior program to Bali mandara is the Government's idea to provide Improvement of the quality of society for the better in the future. This is still an important thing by the government to realize the Program in Bali Province. This program is addressed by providing Positive benefits for the people of Bali Province, Provincial Government Needs Attention from the Government, the public and the government in the development program of superior Balinese BALI IN Bali Province. Keyword: Bali, Mandara, Economic, Welfare.